Hubungan Pelaksanaan Discharge Planning Terhadap Pengetahuan dan Sikap Keluarga Merawat Pasien Pasca Operasi Sectio Caesarea - Ghina Nur Fadlah; Tetet Kartilah; Ridwan Kustiawan; Peni Cahyati (Pelantar Press, 2026)
Discharge planning is an important process in patient care, particularly for patients after cesarean section surgery, with the aim of improving family understanding in providing home care and preventing complications and readmissions. This study aimed to determine the relationship between the implementation of discharge planning and the knowledge and attitudes of families in caring for post-cesarean patients at Dr. Soekardjo Regional General Hospital. Theories underlying this research included discharge planning, knowledge, and attitudes, as well as implementation principles for post-cesarean patients. This study used a quantitative method with a cross-sectional approach, involving 25 respondents selected using a total sampling technique. The research instrument was a questionnaire that had been tested for validity and reliability. The results showed that most respondents rated the implementation of discharge planning as good (60%), with a high level of knowledge (64%) and predominantly positive family attitudes (60%). Bivariate analysis using Fisher’s Exact Test showed a significant relationship between discharge planning implementation and knowledge (p = 0.000) as well as family attitudes (p = 0.000). This study concludes that effective discharge planning is significantly related to family knowledge and attitudes. It is recommended that health care providers implement discharge planning in structured, communicative, continuous care programs